2022
DOI: 10.3389/fneur.2021.791545
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Newly Developed Smartphone App for Risk Factor Management in Young Patients With Ischemic Stroke: A Pilot Study

Abstract: Background: Efficient treatment of modifiable vascular risk factors decreases reoccurrence of ischemic stroke, which is of uttermost importance in younger patients. In this longitudinal pilot study, we thus assessed the effect of a newly developed smartphone app for risk factor management in such a cohort.Methods: The app conveys key facts about stroke, provides motivational support for a healthy lifestyle, and a reminder function for medication intake and blood pressure measurement. Between January 2019 and F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…Many Apps aim to help patients manage their risk factors. The PRESTRO App [ 67 ] combines motivational support for a healthy lifestyle (physical activity, healthy nutrition, and smoking cessation), a reminder function for medication intake and blood pressure measurement and stroke education. Results from Fruhwirth et al [ 67 ], clinical trial show that patients in the intervention group reported to be physically almost twice as active (13±9 hour/week) compared to controls (7±5 hour/week; P =0.022).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many Apps aim to help patients manage their risk factors. The PRESTRO App [ 67 ] combines motivational support for a healthy lifestyle (physical activity, healthy nutrition, and smoking cessation), a reminder function for medication intake and blood pressure measurement and stroke education. Results from Fruhwirth et al [ 67 ], clinical trial show that patients in the intervention group reported to be physically almost twice as active (13±9 hour/week) compared to controls (7±5 hour/week; P =0.022).…”
Section: Resultsmentioning
confidence: 99%
“…The PRESTRO App [ 67 ] combines motivational support for a healthy lifestyle (physical activity, healthy nutrition, and smoking cessation), a reminder function for medication intake and blood pressure measurement and stroke education. Results from Fruhwirth et al [ 67 ], clinical trial show that patients in the intervention group reported to be physically almost twice as active (13±9 hour/week) compared to controls (7±5 hour/week; P =0.022). More intense App usage was strongly associated with higher physical activity (r=0.60, P =0.005) and lower consumption of unhealthy food (r=−0.51, P =0.023).…”
Section: Resultsmentioning
confidence: 99%
“…Studies were conducted across 20 different countries, with the majority conducted in the United States (n = 14) [ 38 , 42 45 , 50 , 57 , 59 , 67 , 74 , 81 – 83 , 88 ] and China (n = 11) [ 40 , 46 , 73 , 76 80 , 84 86 ]. Other countries included the United Kingdom (n = 4) [ 63 , 64 , 69 , 72 ], South Korea (n = 2) [ 55 , 56 ], Australia (n = 2) [ 41 , 65 ], Belgium (n = 2) [ 54 , 75 ], Germany (n = 2) [ 49 , 60 ], Ghana (n = 2) [ 68 , 89 ], Hong Kong (n = 2) [ 70 , 71 ], India (n = 2) [ 34 , 39 ], Malaysia (n = 2) [ 35 , 87 ], New Zealand (n = 2) [ 36 , 61 ], Pakistan (n = 2) [ 52 , 53 ], Austria (n = 1) [ 47 ], Denmark (n = 1) [ 48 ], France (n = 1) [ 37 ], Israel (n = 1) [ 62 ], Japan (n = 1) [ 66 ], Thailand (n = 1) [ 58 ], and Turkey (n = 1) [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…The majority of articles reported the sex (n = 32) [ 34 , 38 , 41 , 43 49 , 52 , 53 , 56 , 57 , 59 , 61 , 65 , 66 , 68 74 , 77 79 , 84 86 , 88 ] or gender (n = 19) [ 35 , 37 , 39 , 40 , 42 , 51 , 54 , 55 , 58 , 60 , 62 , 63 , 75 , 76 , 80 83 , 87 ] of participants, but no articles reported both sex and gender. Level of education was reported by 29 articles [ 35 , 36 , 39 , 42 , 45 , 47 , 50 53 , 55 , 58 , 59 , 62 , 68 , 70 , 71 , 73 , 74 ,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation